2020
DOI: 10.1016/j.ebiom.2020.102643
|View full text |Cite
|
Sign up to set email alerts
|

Urinary TERT promoter mutations are detectable up to 10 years prior to clinical diagnosis of bladder cancer: Evidence from the Golestan Cohort Study

Abstract: Background: Detecting pre-clinical bladder cancer (BC) using urinary biomarkers may provide a valuable opportunity for screening and management. Telomerase reverse transcriptase (TERT) promoter mutations detectable in urine have emerged as promising BC biomarkers. Methods: We performed a nested case-control study within the population-based prospective Golestan Cohort Study (50,045 participants, followed up to 14 years) and assessed TERT promoter mutations in baseline urine samples from 38 asymptomatic individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 30 publications
5
44
0
Order By: Relevance
“…TERT promoter mutations were detected in 14 pre-clinical cases (sensitivity 46.67%) and none of the controls (specificity 100.00%). Most notably, the mutations were detectable up to 10 years prior to clinical diagnosis, indicating that detecting pre-clinical BC using cost-effective urinary TERT biomarkers may provide a valuable opportunity for BC screening and management [ 11 ].…”
Section: Urinary Tert Promoter Mutations: the Hmentioning
confidence: 99%
See 2 more Smart Citations
“…TERT promoter mutations were detected in 14 pre-clinical cases (sensitivity 46.67%) and none of the controls (specificity 100.00%). Most notably, the mutations were detectable up to 10 years prior to clinical diagnosis, indicating that detecting pre-clinical BC using cost-effective urinary TERT biomarkers may provide a valuable opportunity for BC screening and management [ 11 ].…”
Section: Urinary Tert Promoter Mutations: the Hmentioning
confidence: 99%
“…The average costs of cystoscopy are around $206, and the cost of non-invasive urine cytology is around $56 [ 87 ]. By contrast, the cost of the NGS-based and ddPCR assays for detecting urinary TERT promoter mutations in bladder cancer developed by our group [ 10 , 11 ] is about 24€ per sample, and, therefore, has the potential to be easily implemented for cost-effective bladder cancer management strategies.…”
Section: Urinary Tert Promoter Mutations: the Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study has shown an increased risk associated with the detection of these mutations and recurrence of pT1 bladder cancer [24] and a more recent one demonstrated that the post-therapy urinary C228T status in BC cases under surveillance for relapse matched the clinical observations [19] thereby suggesting a plausible way of non-invasive dynamic follow-up of non-muscle invasive bladder cancer patients. In addition, within a prospective cohort study, urinary TERT promoter mutations were detected up to 10 years prior to clinical diagnosis of primary bladder cancer and were absent from matched controls [12]. All these studies provide exciting evidence for the utility of urinary TERT promoter mutations as non-invasive biomarkers for bladder cancer detection and monitoring.…”
Section: Discussionmentioning
confidence: 94%
“…We have recently developed a Next-Generation Sequencing (NGS)-based assay, called UroMuTERT, for the comprehensive detection of BC in urine cell pellet and cell-free DNA samples [11]. We specifically showed in case-control studies that urinary TERT promoter mutations have excellent sensitivity and specificity for the detection of BC [11] and that these mutations could also be detected in urinary DNA of asymptomatic individuals years prior to primary diagnosis of BC with high specificity [12], highlighting their potential to be used as simple and inexpensive non-invasive biomarkers for early detection of BC. While the NGS assay shows great promise in detecting TERT promoter mutations in urine samples, the complex laboratory workflow and requirement of extensive bioinformatics skills for data analysis are still considered as a bottleneck for their large-scale clinical application.…”
Section: Introductionmentioning
confidence: 99%